Distortions on Cameroon’s War-Time Economy, 1914-1916 - Achenui, Nwenfor (American Journal of International Relations, 2021)
Purpose. The paper examines the degree of turbulence that was meted on the colonial economy of the Cameroons between 1914-1916. Methodology: The study was built on the theoretical method, garnered largely from secondary sources, and an analytical pattern that is highly conventional. Results: The indicated that wartime conditions led to increased distortions on Cameroon's economic patterns especially in the form of higher taxations, agricultural shifts and restrictive trading regulations and concluded that this metropolitan based economy was literally altered to pilot allied war efforts. Unique contribution to theory and practice: The paper recommends that, a shift from the archaic system of bitter revanchist that placed nation-states at war with each other as a necessary corollary for imperial expansion, for a more peaceful approach to cross country rifts, would lessen future tensions and make futile any eminent war with bitter lessons on world economies even as national rivalries persist until the 21st century.